Marine particle size distribution data obtained with an Underwater Vision Profiler 6 mounted on BGC Argo float WMO6904139 - Rainer Kiko; Lars Stemmann; Edouard Leymarie; Antoine Poiteau; Herv Claustre; Camille Catallano; Marc Picheral (PANGAEA, 2023)
Here we provide particle size and biovolume distribution data from an Underwater Vision Profiler 6, mounted on a BGC Argo Float with the WMO number 6904139. The float was deployed at the Atlantic Equator on the 14 July 2021 at 0.01 degree South, 23.04 degree West. Parking depth was set at 1000 m and profiling depth to 2000 m. Profiling frequency was every three days. The float moved east and stayed always very close to the equator until it was deliberately picked up on the 23 March 2022 at 0.03 degrees North and 7.39 degrees West.